Fate and chemical speciation of antimony (Sb) during uptake, translocation and storage by rye grass using XANES spectroscopy. (December 2017) - Ji, Ying; Sarret, Géraldine; Schulin, Rainer; Tandy, Susan
Abstract: Antimony (Sb) is a contaminant of increased prevalence in the environment, but there is little knowledge about the mechanisms of its uptake and translocation within plants. Here, we applied for the synchrotron based X-ray absorption near-edge structure (XANES) spectroscopy to analyze the speciation of Sb in roots and shoots of rye grass ( Lolium perenne L. Calibra). Seedlings were grown in nutrient solutions to which either antimonite (Sb(III)), antimonate (Sb(V)) or trimethyl-Sb(V) (TMSb) were added. While exposure to Sb(III) led to around 100 times higher Sb accumulation in the roots than the other two treatments, there was no difference in total Sb in the shoots. Antimony taken up in the Sb(III) treatment was mainly found as Sb-thiol complexes (roots: >76% and shoots: 60%), suggesting detoxification reactions with compounds such as glutathione and phytochelatins. No reduction of accumulated Sb(V) was found in the roots, but half of the translocated Sb was reduced to Sb(III) in the Sb(V) treatment. Antimony accumulated in the TMSb treatment remained in the methylated form in the roots. By synchrotron based XANES spectroscopy, we were able to distinguish the major Sb compounds in plant tissue under different Sb treatments. The results help to understand the translocation and transformation of different Sb species in plants after uptake and provide information for risk assessment of plant growth in Sb contaminated soils. Graphical abstract: Schematic diagram of suggested Sb uptake and transfer routes in the roots and shoots of ryegrass. iSb = inorganic Sb, TMSb = trimethyl-Sb(V), GSH represents any thiol group including phytochelatins and glutathione, Sb(III)-GSH represents Sb(III)-thiol complexes. Highlights: Sb speciation of rye grass with low concentrations was measured by XANES. Uptake of Sb(III) resulted in a Sb(III)-thiol complexes as a means to detoxify Sb. Oxidation of Sb(III) to Sb(V) might be an alternative detoxification method in roots. Sb(V) was reduced to Sb(III) in shoots when plants were treated with Sb(V). Abstract : Application of XANES spectroscopy to Sb(III), Sb(V) or TMSb treated rye grass allowed discrimination between Sb oxidation states and Sb-thiol complexes in rye grass.